Mengelola Kinerja dengan Perspektif Gender: Analisis Pengembangan Karir, Reward, dan Punishment - Almas Farah Dinna Dewi; Dewi Shinta Kumalasari; Sri Wahyu Lelly Hana Setyanti (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the influence of career development, rewards, and punishment on the performance of ASN employees at BKPSDM Jember, with a focus on gender perspectives in performance management. It explores how each factor contributes to employee performance and examines gender-based differences in perception and impact. Methodology: A quantitative approach was used with total sampling of 48 ASN employees at BKPSDM Jember. Data were collected through questionnaires (primary data) and institutional records (secondary data), then analyzed using multiple linear regression, t-tests, and f-tests. An independent sample t-test was used to examine gender-based perception differences. Results: Results: The t-test shows that career development (sig. 0.020), reward (sig. 0.006), and punishment (sig. 0.004) significantly influence employee performance. The f-test confirms the simultaneous influence of all three variables, with F = 10.889 greater than F_table = 2.82, and significance value of 0.000, which is less than 0.05. Gender-based differences were found in perceptions of rewards and performance, where male employees reported higher average scores. However, no significant gender differences were identified in perceptions of career development and punishment. Conclusion: Career development, rewards, and punishments positively impact employee performance. Gender disparities in perception of rewards and performance suggest a need for more inclusive and equitable HR practices. Limitations: The small sample size (48 employees) limits generalizability. The study also lacks qualitative insights into the underlying causes of perception differences. Contribution: This research provides valuable insights into performance management of civil servants and offers practical guidance for designing gender-responsive HR policies at BKPSDM Jember.